Atomic‐Scale Mechanism of Spontaneous Polarity Inversion in AlN on Nonpolar Sapphire Substrate Grown by MOCVD (Small 16/2022). Issue 16 (21st April 2022) - Liu, Zhiqiang; Liu, Bingyao; Ren, Fang; Yin, Yue; Zhang, Shuo; Liang, Meng; Dou, Zhipeng; Liu, Zhetong; Yang, Shenyuan; Yan, Jianchang; Wei, Tongbo; Yi, Xiaoyan; et al.
Abstract : Spontaneous Lattice Inversion In article number 2200057, Zhiqiang Liu, Shenyuan Yang, Yong Zhang, Peng Gao, and co‐workers confirm the polarity of AlN on sapphire prepared by metal–organic chemical vapor deposition is not inherited from the nitrides/sapphire interface as widely accepted, instead, experiences a spontaneous polarity inversion. Furthermore, a vertical 2D electron gas is revealed at the polarity inversion interface. This work identifies a new origin of high‐density defects in nitride epilayers. It also points to a direction for polarity manipulation and hetero‐polarity device design.